A possible signature of new physics at BES- - 邹佳恒 李海波 张学尧 (Chinese physics C, 2009)
The recent observations of the purely leptonic decay Ds＋→μ＋νμ and τ＋ντ at CLEO-c and B factory may allow a possible contribution from a charged Higgs boson. One such measurement of the decay constant fD. differs from the most precise unquenched lattice QCD calculation by a level of 4 σ. Meanwhile, the measured ratio, BR（Ds＋→μ＋νμ）/BR（D＋→μ＋νμ）, is larger than the standard model prediction at a 2.0σ level. We discuss that the precise measurement of the ratio BR（Ds＋→μ＋νμ）/BR（D＋→μ＋νμ） at BES-Ⅲ will shed light on the presence of new intermediate particles by comparing the data with the theoretical predictions, especially, the predictions of high precise unquenched lattice QCD calculations.